IGF-1 Deficiency Impairs Cerebral Myogenic Autoregulation in Hypertensive Mice. Issue 12 (December 2014) - Toth, Peter; Tucsek, Zsuzsanna; Tarantini, Stefano; Sosnowska, Danuta; Gautam, Tripti; Mitschelen, Matthew; Koller, Akos; Sonntag, William E; Csiszar, Anna; Ungvari, Zoltan
Aging impairs autoregulatory protection in the brain, exacerbating hypertension-induced cerebromicrovascular injury, neuroinflammation, and development of vascular cognitive impairment. Despite the importance of the age-related decline in circulating insulin-like growth factor-1 (IGF-1) levels in cerebrovascular aging, the effects of IGF-1 deficiency on functional adaptation of cerebral arteries to high blood pressure remain elusive. To determine whether IGF-1 deficiency impairs autoregulatory protection, hypertension was induced in control and IGF-1-deficient mice ( Igf1 f/f +TBG-iCre-AAV8) by chronic infusion of angiotensin-II. In hypertensive control mice, cerebral blood flow (CBF) autoregulation was extended to higher pressure values and the pressure-induced tone of middle cerebral arteries (MCAs) was increased. In hypertensive IGF-1-deficient mice, autoregulation was markedly disrupted, and MCAs did not show adaptive increases in myogenic tone. In control mice, the mechanism of adaptation to hypertension involved upregulation of TRPC channels in MCAs and this mechanism was impaired in hypertensive IGF-1-deficient mice. Likely downstream consequences of cerebrovascular autoregulatory dysfunction in hypertensive IGF-1-deficient mice included exacerbated disruption of the blood-brain barrier and neuroinflammation (microglia activation and upregulation of proinflammatory cytokines and chemokines), which were associated with impaired hippocampal cognitive function. Collectively, IGF-1 deficiency impairs autoregulatory protection in the brain of hypertensive mice, potentially exacerbating cerebromicrovascular injury and neuroinflammation mimicking the aging phenotype.